2013
DOI: 10.1007/978-1-62703-302-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Resistance to Cisplatin and Other Anticancer Drugs and the Role of Sphingolipid Metabolism

Abstract: Summary Dictyostelium discoideum has proven to be a useful lead genetic system for identifying novel genes and pathways responsible for the regulation of sensitivity to the widely used anti-cancer drug cisplatin. Resistance to cisplatin is a major factor limiting the efficacy of the drug in treating many types of cancer. Studies using unbiased insertional mutagenesis in D. discoideum have identified the pathway of sphingolipid metabolism as a key regulator in controlling sensitivity to cisplatin. Using the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, the clinical use of cisplatin is limited due to its side-effects and drug resistance (17)(18)(19). The antitumor activity of cisplatin is attributed to its ability to cause DNA damage, leading to the subsequent induction of apoptosis (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical use of cisplatin is limited due to its side-effects and drug resistance (17)(18)(19). The antitumor activity of cisplatin is attributed to its ability to cause DNA damage, leading to the subsequent induction of apoptosis (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of Dictyostelium cells for drug screening and pharmacogenetic studies had been illustrated in the past with studies with aminobisphosphonate, cisplatin, valproic acid and lithium (Alexander et al, 2013;Otto et al, 2016). These studies have now been extended to the characterization of curcumin and naringenin, which were found to inhibit development and/or growth (Cocorocchio et al, 2018;Swatson et al, 2017;Garige and Walters, 2015;Waheed et al, 2014).…”
Section: Dictyostelium As a Model For Biomedical Research: Recent Conmentioning
confidence: 99%
“…Several studies have shown the importance of targeting SphK to modulate sphingomyelin metabolsim in cancer therapy and in the treatment of several other diseases in animal models. Furthermore, the implication of sphingolipids in the development of MDR by cancer cells seems to be sufficiently proven and several reviews about this subject have been published. ,, Among these sphingolipids, the SphK and some of their receptors have presented a relation with the MDR phenomena. , These inter-relationship results are particularly relevant to SphK1. Therefore, the demonstrated role of SphKs, particularly SphK1, in the development of MDR by cancer cells makes these kinases an attractive target in developing effective therapeutics to fight against cancer.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Furthermore, the implication of sphingolipids in the development of MDR by cancer cells seems to be sufficiently proven and several reviews about this subject have been published. 21,27,135 Among these sphingolipids, the SphK and some of their receptors have presented a relation with the MDR phenomena. 136,137 These inter-relationship results are particularly relevant to SphK1.…”
Section: ■ Summary and Perspectivesmentioning
confidence: 99%